Comments on Naum Jasny's "Soviet Statistics" - Gerschenkron, Alexander; Marx, Daniel (The Review of Economics and Statistics, 1950)
N his article, Statistics, Mr. Jasny provides a number of examples designed to demonstrate the manifold ways in which official Soviet statistics are manipulated to produce the impression of achievements greater than those actually attained. Most of these examples are not new and have been frequently mentioned in Western economic literature on Soviet Russia. The justification for publishing an article of this sort therefore must lie in its concluding remarks, in which Mr. Jasny attacks Professor Bergson and myself. Through a series of quotations torn out of context, Mr. Jasny tries to create the impression that in the opinion of those he criticizes Soviet statistics are free of manipulation and can be confidently accepted at their face value. This inference is highly misleading. Mr. Jasny neglects entirely to point out that the passages he criticizes are gleaned from articles the very purpose of which was to present critical analyses of the original Soviet data. The meaning of these passages therefore is altogether different from the one imputed to them by Mr. Jasny. Anyone dealing with Soviet statistics must begin by considering the possibility that the figures may represent sheer invention. If this were the case, no analysis would be possible. The purpose of the remarks which have provoked Mr. Jasny's displeasure was to place on record the view that Soviet statistics are not freely invented; that as a rule they have meaning and significance, although the form in which they are presented requires great caution in dealing with them. This and only this was suggested. Mr. Jasny's own extensive use of Soviet statistics shows that he shares this view. No unbiased reader could have missed this point. Nor, I venture to suggest, has Mr. jasny. For after havlng charged Professor Bergson and myself with uncritical acceptance of Soviet data, he continues: